The Reformation Canon and the Development of Biblical Scholarship - Lang, Marijke Hélène de (The Bible translator, 2016)
This paper argues that the well-intended attention of humanist and Reformation scholars to the original languages of the Bible also had its downside, especially for study of the New Testament. Although the revival of Greek and Hebrew studies in itself was a positive development, together with the promotion of a Hebrew canon and the notion of sola scriptura, the hermeneutical horizon of the New Testament was limited to a Hebrew canon and a Semitic context. The New Testament was separated from its original Hellenistic-Jewish Greek environment, and was explained from a background to which it never really belonged.